Determination of the adequate dosage of the soil-cement, using clay of high plasticity (2019)
The clay is used in the area of constructions, ceramics and industrial applications: insecticides, pharmaceutical industry, cosmetics and painting, for its physical and chemical properties that are suitable for different civil projects (roads, public services network, constructions); the dosage is a technique to modify and improve the conditions of the soil-cement in reference to the resistance, conditions of insolubility, impermeability, durability and appearance. In this study, high plasticity clay was evaluated through different laboratory tests (humidity test, soil liquid limit, plasticity index, granulometric analysis, California Bearing Ratio) for three samples and specifying the methodology used in each step, with the objective of knowing its structure and functioning in rural roads in combination with soil-cement, looking for a more profitable and lasting option in this sector, in order to benefit the people surrounding these sectors, improving the income of the sector and seeking to mitigate the environmental impact.